Development, optimization, and invitro evaluation of novel fast dissolving oral films (FDOF's) of Uncaria tomentosa extract to treat osteoarthritis - J. Naga Sowjanya; P.Raja Rao (Heliyon, 2023)
Fast dissolving oral films(FDOF's) are the popular dosage forms when placed in the oral cavity, disintegrate rapidly and dissolve to release the medication for improving oral absorption. Traditionally Uncaria tomentosa plant is used in the treatment of rheumatoid arthritis as Non-steroidal Anti-inflammatory agent along with analgesic properties. The plant extract is reported to be used in low dose as analgesic and anti-inflammatory agent in Rheumatoid Arthritis. No scientific data was reported on Uncaria plant formulation as FDOF's for treating osteoarthritis. This study aims to formulate fast oral dissolving film(FDOFs) Uncaria tomentosa bark extract and evaluate using Invitro studies for osteoarthritis. About 14 formulations were prepared using standard Box Behnken design protocol for optimization using the natural film formers, synthetic polymers, super disintegrants, plasticizers as independent variables with folding endurance and disintegration time as dependent variables by solvent casting method. Further the formulation characteristics including physical and mechanical behavior of films and drug release behavior was evaluated. The 3D countour plots and response curves suing the design expert software were investigated which proved that the optimized oral dissolving films of extract with Pullalan gum, HPMC (polymers), Propylene glycol, PEG 400 (Co-solvents) and Croscarmellose sodium (super Disintegrant) are stable and uniform with formulation characteristics. The drug release rates prove that F5 and F13 formulations showed 99.90% drug release within 30 min following first order kinetics with satisfactory mechanical properties. The study results suggest that the fast dissolving oral films of Uncaria tomentosa extract is novel, attractive and alternative to the available marketed products resulting in improved patient adherence in treatment of osteoarthritis.